ANALYSIS OF THE FUNCTIONAL CHARACTERISTICS OF ANTHROPONYMS IN THE CONTEXT OF THE NOVEL BEING HUMAN IS DIFFICULT - S.B.Khursankulov; D.Z.Abduazimova (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article analyzes the functional aspects of anthroponyms used in O‘lmas  Umarbekov’s  novel  “Odam  bo‘lish  qiyin”  and  highlights  their  role  in portraying character traits. In addition, the author’s individual skill in selecting names is  examined  and  evaluated.  The  results  of  the  study  contribute  to  enriching  the theoretical and practical foundations of ongoing and future research in the fields of literary text linguistics and onomastics.